Electrochemical Recycling of Photovoltaic Modules to Recover Metals and Silicon Wafers. Issue 11 (30th September 2021) - Modrzynski, Christian; Blaesing, Luisa; Hippmann, Sebastian; Bertau, Martin; Bloh, Jonathan Z.; Weidlich, Claudia
Abstract: An electrochemical‐assisted leaching process using boron‐doped diamond (BDD) electrodes was developed to recover valuable metals from photovoltaic modules. With BDD electrodes peroxydisulfate is generated from sulfuric acid to oxidatively dissolve copper, tin and silver from solar cell contacts. Since the oxidant is regenerated in the developed process, no additional hazardous and volatile chemicals are required, and the process can be operated solely by electricity. In addition, the dissolved metals can be electrochemically recovered at the cathode of the same cell. Abstract : Silver, copper and tin were leached from photovoltaic modules by using boron‐doped diamond electrodes to generate peroxydisulfate as oxidant from sulfuric acid. The dissolved metals were then recovered by electrowinning them within the same cell. Thus, the process can be driven solely by electricity without the addition of further chemicals.